KAJIAN ANALISIS NUTRISI KEDELAI HITAM (GLYCINE SOJA (L) MERRIT) DIFERMENTASI OLEH RHIZOPUS OLIGOSPORUS, ASPERGILLUS SOJAE DAN KONSORSIUMNYA TERHADAP KARBOHIDRAT DAN LEMAK - Ida Ningrumsari Ningrumsari; R Budiasih; Putri Afrilliyanti (Ma'soem University, 2022)
One of the uses of black soybeans is to make soy sauce, the purpose of this research is to analyze the nutrition of carbohydrates and fats in black soybeans. The research method used a completely randomized design (CRD) with a 3x3x3 factorial pattern with 3 replications. The first factor consists of the type of microbe (M) namely m1 = R oligosporus, m2 = A sojae, m3 = m1 + m2, the second factor is fermentation time (W) consisting of w1 = 48 hours, m2 = 96 hours and m3 = 144 hours and the third factor, namely (D) consists of d1 = 2 grams, d2 = 3 grams and d3 = 4 grams. Existing data were collected to be processed by analysis of variance (Anova). If there is a significant difference to the control, it is continued with Duncan's multiple distance test. The results showed that the carbohydrate content in black soybeans decreased with the influence of the m3 microbe (the consortium, namely R oligodporus + A sojae) by 13.87%, with a dose of d1 inoculum (2 grams) of 25.53% with a fermentation time of w3 (144 hours). ) of 22.12%. To reduce the carbohydrate content, the best method is m3w3d1(R oligosporus + A sojae, with a fermentation time of 144 hours and an inoculum dose of 2 grams). The fat content of black soybeans increased with the effect of the interaction of microbial types and fermentation time on the increase in fat found in m1w1 of 31.01%. The effect of the interaction of microbial species and inoculum dose on the increase in fat was found in m1d1 of 28.61%. The best fat increase was m1w1d1 (R oligosporus, 48 hours fermentation time with 2 gram inoculum dose).